Clinical and economic burden associated with stage III to IV triple‐negative breast cancer: A SEER‐Medicare historical cohort study in elderly women in the United States. Issue 10 (5th March 2018) - Schwartz, Kendra L.; Simon, Michael S.; Bylsma, Lauren C.; Ruterbusch, Julie J.; Beebe‐Dimmer, Jennifer L.; Schultz, Neil M.; Flanders, Scott C.; Barlev, Arie; Fryzek, Jon P.; Quek, Ruben G.W.
Abstract : BACKGROUND: The current study was performed to describe patient characteristics, treatment patterns, survival, health care resource use (HRU), and costs among older women in the United States with advanced (American Joint Committee on Cancer stage III/IV) triple‐negative breast cancer (TNBC) in the Surveillance, Epidemiology, and End Results (SEER)‐Medicare database. METHODS: Women who were aged ≥66 years at the time of diagnosis and diagnosed with advanced TNBC between January 1, 2007, and January 1, 2011, in the SEER‐Medicare database and who were followed for survival through December 31, 2013, were eligible. Patient demographic and clinical characteristics at the time of diagnosis, subsequent treatment patterns, and survival outcomes were analyzed. HRU and costs for the first 3 months after diagnosis, the last 3 months of life, and the time in between are summarized. All analyses were stratified by American Joint Committee on Cancer stage of disease. RESULTS: There were 1244 patients newly diagnosed with advanced TNBC; the majority were aged ≥75 years (61% with stage III disease and 57.4% with stage IV disease) and white (>70% of patients in both disease stage groups). The most common treatment approaches were surgery combined with chemotherapy for patients for stage III disease (50.6%) and chemotherapy alone or with radiotherapy for patients with stage IV disease (31.3%). Diverse chemotherapy regimens were administered for each line of therapy; nevertheless, the medications used were consistent with national guidelines. Patients with stage III and stage IV disease were found to have a similar mean number of hospitalizations and outpatient visits, but mean monthly costs were greater for patients with stage IV disease at all 3 time points. The mean cost per patient‐month (in 2013 US dollars) was $4810 for patients with stage III disease and $9159 for patients with stage IV disease. CONCLUSIONS: Among older women with advanced TNBC, significant treatment variations and considerable HRU and costs exist. Further research is needed to find effective treatments with which to reduce the clinical and economic burden of this disease. Cancer 2018;124:2104‐14 . © 2018 American Cancer Society . Abstract : This cohort of older (aged ≥66 years) women with American Joint Committee on Cancer stage III/IV triple‐negative breast cancer from the US Surveillance, Epidemiology, and End Results (SEER)‐Medicare database demonstrated significant variations in treatment patterns. The mean cost per patient‐month of health resource use was $4810 for patients with stage III disease and $9159 for patients with stage IV disease.